خصائص الاستعارة في القرآن )دراسة تحليلية تطصائص الاستعارات في سورة البقرة وآل عمران والنساء وتضمينها التًبوي( - Abdul Hadi (Jurnal Pendidikan Islam, 2013)
This study started from the assumption that isti'ârah widely used in the Qur'an and has the essential elements of interest to be investigated further, especially in Sura al-Baqarah, Ali Imran and An-Nisa. The purpose of this study is to find the letter isti'ârah characteristics and its influence on the meaning of the verse. The method used in this study is descriptive method, to explain in depth the meaning of the words used and selected based on its context in the Qur'an. The results of this study it can be concluded that the media is seen as isti'arah Qur'an to convey the message of Allah to mankind by way of revealing the relationship between the meaning isti'arah with the intended meaning in the verses of the Koran. In terms of education, isti'arah also very useful to use in teaching and learning, particularly useful in helping teachers and textbooks so easily understood by students.